EARTH SEWING TECHNIQUE FOR THE PRESERVATION OF FANASAKO HISTORICAL KILN SITES - X. J. Chai; S. Hayashi; Y. J. Du (Lowland Technology International, 2004)
The Funasako historical klin sites, which are located in the northern part Kyushu Island in Japan, have been considered as public exhibition areas. This requires preservation of the kiln remains by reinforcement of the soil. Considering the complicated local topography, the reinforcement method that was proposed is a combination of chemical grouting and soil nailing, and is termed the Earth Sewing Technique (EST) in this paper. In order to prevent disturbance of the soil in the kiln remains, a drilling hole diameter for soil nailing of 7 mm with a tendon (bolt) that has a diameter of 3 mm was selected. Field full-scale pullout test at a model kiln site were carried out before applying the reinforcement technique to the real historical kiln sites. This paper presents the field pullout results and the results of a series of laboratory pullout test that were conducted to investigate the critical factors affecting the perfomance of the EST. Design parameters have been recommended based on rational interpretation of the field and laboratory pullout test results. The pullout strength-water content relationships were found to be very useful for understanding and evaluating the shear strength capacity of soil nailing in partially saturated cohesive soils.